PERAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR PESERTA DIDIK SEKOLAH DASAR - Revi Mariska; Deviyanti Pangestu; Yoga Fernando Rizqi; Riswanti Rini (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to describe the use of school libraries as a learning resource at BPK Penabur MetroChristian Elementary School. This type of qualitative research uses a descriptive method. The datacollection technique was carried out by purposive sampling. The sources of research data are schoolprincipals, library officers, educators, students, and parents. Data collection techniques are carried outby means of observation, interviews, and documentation. The results of the study show that (1) themanagement of the library is running well which can be seen from the existence of facilities, maintenanceand care, and book collections, even though the collection of nonfiction books itself has not reached theideal percentage, (2) the utilization of the library has been running well as can be seen from the openinghours of services, the frequency of visits, the most used types of books, the access to loans offered, and theexistence of a reading corner in each class that supports, (3) the role of educators in the use of librarieshas been running well can be seen from the strategies and actions of educators in motivating students inthe use of libraries (4) the efforts of the principal in completing school library facilities, namely byproposing funding sources to the foundation for the purchase of books, shelves, desks, and computers, aswell as inventorying and repairing damaged library facilities and provision of a comfortable schoollibrary room, (5) the most inhibiting and supporting factors for the use of libraries are found in externalfactors, namely the lack of spaciousness of the library building and limited visiting time as an inhibitingfactor and varied books and the enthusiasm of students as supporting factors.Keywords: Utilization, Library, Learning Resources